Factors Influencing Contraceptive Usage Among Women Childbearing Age in Indonesia (Analysis of The 2023 Indonesian Health Survey) - Amrina Rosyada; Agnes Intan Feronika (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
The global trend of Total Fertility Rate (TFR) has significantly decreased, particularly in developed and some developing countries. Controlling the population growth rate could be achieved by suppressing fertility through the use of contraceptives. This study utilized secondary data from SKI 2023 with a cross-sectional design. Sampling was conducted using multistage random sampling, resulting in a total sample of 53,783 respondents. The sample consisted of Women of Reproductive Age, aged 15-49 years in Indonesia, who met the inclusion criteria. Data analysis included univariate, bivariate, and multivariate analyses using complex sample procedures. The results showed that the prevalence of contraceptive use among women of reproductive age was 72.4%. The multivariate analysis revealed several factors significantly associated with contraceptive use, including age at first pregnancy (p = 0.001; PR = 1.365; 95% CI: 1.259-1.480), occupation (p = 0.001; PR = 1.289; 95% CI: 1.210-1.372), economic status (p = 0.008; PR = 1.098; 95% CI: 1.025-1.177), place of residence (p = 0.001; PR = 1.198; 95% CI: 1.120-1.281), unwanted pregnancy (p = 0.002; PR = 1.231; 95% CI: 1.081-1.401), and parity (p = 0.001; PR = 1.121; 95% CI: 1.050-1.196). The most dominant factor associated with contraceptive use was education level (p = 0.001; PR = 1.489; 95% CI: 1.388-1.596). Women of reproductive age could improve their knowledge about contraceptive use not only through formal education but also by utilizing technology, such as educational videos, webinars, and informative content on social media platforms, to better understand and select appropriate contraceptives based on their health needs and conditions. Keywords: Contraceptives, Influencing Factors, Women Childbearing Age